English Expressions Frequently Used By Indonesian Social Media “X” Users: A Morpho-Semantic Analysis - Siti Azura; Rahmadsyah Rangkuti; Ely Hayati Nasution (Universitas Sebelas Maret, 2025)
This research aims to find types of word formation English expressions frequently used by social media X users in Indonesia and describe how English expressions frequently used by social media X users in Indonesia are interpreted. The approach used in this research is the Morpho-Semantic approach, with word of formation processes theory by Bauer and Semantic theory by Leech as a reference for analysis. The research method used was qualitative method. The techniques of data collection used are reading and documentation study by capturing the screen from X's social media accounts @tanyakanrl and @convomfs. Meanwhile the data analysis design model applied was content analysis, the findings of the research show that, 25 English expressions are used by social media X users in Indonesia. These expressions experience the formation proces,s including 8 compounding, 6 affixations, 6 conversions, 2 blending, and 3 acronyms. Further, from the analysis of the use of English expressions in social media “X” were found 1 reflected, 2 affective, 1 collocative, 1 social, 20 connotative.